Metaforični koncepti ljubezni in ženske v pesniških prvencih slovenske moderne - Čeh Steger, Jožica (Slavia Centralis, 2022)
The present discussion is based on the cognitive understanding of metaphors, examining various metaphorical concepts of love and the female in the poetry of Slovenian ‘moderna’ using examples of the literary debuts Erotika (1899) by Ivan Cankar, Čaša opojnosti (1899) by Oton Župančič and Poezije (1906) by Ljudmila Poljanec, the latter of which was attributed the status of first Slovenian lesbian poet by more recent studies. We seek to demonstrate that the metaphorisation of eroticism and the female reflects various aesthetics of literary streams and stylistic trends of ‘moderna’, as well as discourses of gender and the female, marking the spiritual horizon at the turn of the 20th century. This is also conditioned with the female and male perspective.
Keywords: female images; ljubezenska poezija; love poetry; metafora; metaphor; Slovene "moderna"; slovenska moderna; ženske podobe